Defect engineering mediated ultralow-potential near-infrared electrochemical luminophor as well as preparation method and application of defect engineering mediated ultralow-potential near-infrared electrochemical luminophor
Through defect engineering-mediated perylene-based metal organic framework materials, combined with acid regulator-induced defects and S2O82-co-reaction reagent, an efficient ultra-low potential near-infrared electrochemiluminescent was constructed, solving the slow electrocatalytic kinetics and high interference. The problem of this method is to realize high sensitivity detection of carboxylate esterase activity, providing an effective way for trace biosensing.
Patent Information
- Application Number
- CN202411372183.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
Existing ultra-low potential near-infrared electrochemiluminescent (ULP-NIR ECL) cathode luminescents have application challenges in slow electrocatalytic kinetics and high interference background signals, limiting their sensitivity and accuracy in trace biosensing sex.
Mediated by defect engineering, defect-rich perylene-based metal organic framework material was formed in hydrothermal reaction using 3,4,9,10-perylene tetracarboxylic acid (PTCA) and transition metal salts, combined with acid regulators to induce defects. An efficient ultra-low potential near-infrared electrochemiluminescent was prepared and integrated with S2O82-co-reaction reagent to construct a De-Fe(III)-PTCA MOFs/S2O82-binary ECL luminescence system.
Achieve high sensitivity detection of carboxylate esterase activity, reduce electrochemical interference, and provide low-interference and label-free biosensor, suitable for early diagnosis of carboxylate esterase-related diseases, with a detection limit of 6.6×10-7U /L.
Smart Images

Figure CN119264446A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of analytical chemistry and clinical diagnosis, and relates to the preparation of an ultra-low potential near-infrared electrochemical luminescent body, and specifically refers to an ultra-low potential near-infrared electrochemical luminescent body mediated by defect engineering, and a preparation method and application thereof. Background Art
[0002] Electrochemiluminescence (ECL) is a phenomenon of radiant light produced by the high-energy electron transfer reaction triggered by the electrode interface, which produces an excited state of the luminophore and then transitions back to the ground state. Therefore, ECL analysis technology is a combination of electrochemical and chemiluminescence techniques, with the advantages of fast response, low background signal, high sensitivity, and easy integration. It is currently one of the leading commercial technologies in the field of in vitro diagnostics. The development and screening of high-performance ECL luminophores is the cornerstone of the development of ECL technology. Recently, cathode ECL luminophores have evolved from classic tris(2, 2'-bipyridine)ruthenium to emerging nanomaterials such as polymer carbon nitride, metal nanoclusters, and mesh structures. However, the above ECL luminophores usually produce visible light emission and require extremely negative potentials (relative to Ag / AgCl, more than -1.0 V or even -2.0 V) to trigger efficient ECL to meet the sensitivity requirements of practical applications. Extremely negative potentials lead to the decomposition of water and the generation of singlet oxygen, resulting in severe electrochemical interference, potential damage and crosstalk to biomolecules, and high background signals, thus posing severe challenges to accurate diagnosis. In order to meet these challenges, the development of ultra-low potential-triggered near-infrared electrochemiluminescence (ULP-NIR ECL) cathode luminescent devices is of great significance and urgent need.
[0003] The slow reaction kinetics of coreactant activation is a major challenge hindering the development of ULP-NIR ECL cathodoluminescent devices. Recently, coreactant promoters based on transition metal ion nanomaterials, such as cobalt-iron layered double hydroxides, iron single atom catalysts, a-Fe2O3-Pt, and Cu2MoS4, have been developed to promote the activation process of coreactants to produce more active free radicals. However, the long-range intermolecular electron transfer pathways, resulting in low sensitivity and poor stability, restrict their application in the growing demand for sensitive detection. Reticular luminescent metal-organic frameworks (LMOFs), composed of ordered arrangements of metal atoms and organic ligands, can realize the integration of ECL emitters and coreactant promoters in a unified framework, opening up a promising route for efficient intramolecular electron transfer. Shan's group developed self-enhanced Co-2-MI-ZnTCPP by integrating Co-N as a coreactant promoter and porphyrin as an ECL emitter, achieving efficient ECL in the visible light region (maximum = 606 nm). However, ULP-NIR LMOFs ECL is still in its infancy because insufficient exposure to active metal sites leads to slow electrocatalytic kinetics of LMOFs, limiting its high-sensitivity sensing applications. Recent studies have shown that defect engineering can provide an effective tool to tailor the open metal sites of LMOFs and enhance the covalent activation process of co-reactants. Therefore, the introduction of defects may open up new opportunities for the development of ULP-NIR ECL luminophores, help advance their applications in trace and low-interference biosensors, and is an effective means to solve the above problems and develop new immunodiagnostics. Summary of the invention
[0004] In order to solve the above problems, the present invention proposes an ultra-low potential near-infrared electrochemiluminescent body mediated by defect engineering, and its preparation method and application, which solves the problem of slow electrocatalytic kinetics of LMOFs caused by insufficient exposure of metal active sites. In addition, the prepared ultra-low potential near-infrared electrochemiluminescent body can be applied to low-interference and label-free electrochemiluminescent biosensors, thereby achieving highly sensitive detection of carboxylesterase activity.
[0005] To achieve the above object, the technical solution of the present invention is implemented as follows: A method for preparing an ultra-low potential near-infrared electrochemical luminescent body mediated by defect engineering comprises the following steps: mixing 3,4,9,10-perylenetetracarboxylic acid, a transition metal salt solution and an acid regulator aqueous solution, and then subjecting the mixture to a hydrothermal reaction to obtain the obtained product.
[0006] Among them, 3, 4, 9, 10-perylenetetracarboxylic acid (PTCA) is used as the LMOFs ligand, the transition metal ions in the transition metal salt solution are used as the central metal ions, and the acid is used as a regulator (acid regulator) to induce the formation of defects. The defect engineering-mediated ultra-low potential near-infrared electrochemiluminescent material, also known as defect-rich perylene-based metal-organic framework material, is prepared through a hydrothermal reaction.
[0007] The specific steps of its synthesis are: adding transition metal salt solution, PTCA and acid regulator aqueous solution into a reactor respectively, and then adding deionized water. The obtained mixture is fully mixed under ultrasound for 5 minutes, and then heated in an oven for reaction. The obtained sample is centrifuged and purified, and dried under vacuum to obtain a solid that is a defect-rich perylene-based metal organic framework material.
[0008] The transition metal ion in the above transition metal salt solution is Fe(Ⅱ), Cu(Ⅱ), Co(Ⅱ), Fe(Ⅲ) or Zn(Ⅱ); the acid regulator is phosphoric acid, acetic acid, formic acid, hydrochloric acid, trifluoroacetic acid or benzoic acid.
[0009] The molar ratio of the 3, 4, 9, 10-perylenetetracarboxylic acid, transition metal ions and acid regulator is 1:(0.2-1):(1-1.5).
[0010] The temperature of the hydrothermal reaction is 80-140°C and the time is 1-6h.
[0011] The ultra-low potential near-infrared electrochemical luminescent body prepared by the above preparation method.
[0012] The above-mentioned ultra-low potential near-infrared electrochemiluminescent material is used for the detection of carboxylesterase activity.
[0013] The present invention also provides a ULP-NIR De-Fe(III)-PTCA MOFs / S2O8 2- The binary ECL luminescence system achieves highly sensitive and low-interference detection of carboxylesterase activity, providing a promising new approach for the clinical diagnosis of carboxylesterase-related diseases.
[0014] A biosensor, the working electrode of which comprises the above-mentioned ultra-low potential near-infrared electrochemical luminescent body.
[0015] Furthermore, the above biosensor is used in the detection of carboxylesterase activity.
[0016] Furthermore, the above application includes the following steps: adding the carboxylesterase sample to a solution containing a catalytic substrate and a co-reactant, incubating, and detecting the electrochemiluminescence intensity using the biosensor.
[0017] Furthermore, the catalytic substrate is 1-naphthyl acetate; and the co-reactant is a salt containing persulfate.
[0018] The beneficial effects produced by the present invention are: (1) The present invention uses electron-deficient 3, 4, 9, 10-perylenetetracarboxylic acid as a ligand and combines it with an acid regulator-induced defect strategy to develop a highly efficient near-infrared electrochemiluminescence emitter triggered by ultra-low potential. This not only enables the electrochemiluminescence emitter and the co-reaction promoter to trigger efficient intramolecular electron transfer in a unified porous framework, reducing the quenching effect caused by aggregation, but also provides abundant open metal sites, effectively catalyzing the co-reaction reagent, generating abundant active free radicals, significantly reducing the interference of electrochemical side reactions in aqueous solution systems, and promoting applications in low-interference and high-sensitivity imaging and sensing.
[0019] (2) Carboxylesterase was selected as a model analyte, De-Fe(Ⅲ)-PTCA MOFs was used as an electrochemiluminescent body, and 1-naphthyl acetate was used as a selective catalytic substrate to construct a low-interference and label-free electrochemiluminescent biosensor for highly sensitive detection of carboxylesterase activity. The logarithm of carboxylesterase activity in the biosensor was strongly correlated with the reduction in electrochemiluminescence intensity compared to the blank intensity ( R 2 =0.996), the linear regression equation is: Δ I ECL =2051.20 lg(c / U·L -1 )+13045.89; and the detection limit of the carboxylesterase activity of the sensor is 6.6×10 -7 The above-mentioned highly sensitive sensor for detecting carboxylesterase activity provides a promising approach for low-interference and accurate early diagnosis of diseases including hepatocellular carcinoma. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 Schematic diagram of the preparation of defect-rich perylene-based metal-organic framework light-emitting bodies.
[0022] Figure 2The figures are scanning electron microscope spectra, where (a) is the original PTCA assembly; (b) is the Fe(III)-PTCA MOFs without defect regulation prepared in Comparative Example 1; and (c) is the De-Fe(III)-PTCA MOFs prepared in Example 1.
[0023] Figure 3 X-ray photoelectron spectra of De-Fe(III)-PTCA MOFs prepared in Example 1, wherein (a) is the full spectrum of De-Fe(III)-PTCA MOFs; (b) is the high-resolution spectrum of O 1s in De-Fe(III)-PTCA MOFs; and (c) is the high-resolution spectrum of Fe2p in De-Fe(III)-PTCA MOFs.
[0024] Figure 4 Fourier transform infrared spectra of De-Fe(III)-PTCA MOFs prepared in Example 1, Fe(III)-PTCA MOFs prepared in Comparative Example 1, and PTCA.
[0025] Figure 5 Thermogravimetric curves of De-Fe(Ⅲ)-PTCA MOFs and Fe(Ⅲ)-PTCA MOFs.
[0026] Figure 6 For metal ion regulation, in the presence of 20 mmol / L S2O8 2- PTCA / S2O8 in 0.1 mol / L PBS (pH 7.4) 2- 、De-Fe(Ⅱ)-PTCA MOFs / S2O8 2- 、De-Zn(Ⅱ)-PTCA MOFs / S2O8 2- 、De-Co(Ⅱ) / PTCAMOFs / S2O8 2- 、De-Cu(Ⅱ)-PTCA MOFs / S2O8 2- 、De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- Comparison of electrochemiluminescence signals.
[0027] Figure 7 To adjust the performance of De-Fe(Ⅲ)-PTCA MOFs / S2O8, different acid regulators were used. 2- of the electrochemiluminescence performance.
[0028] Figure 8 For the optimization of synthesis conditions, (A) is the optimization of Fe 3+ and PTCA precursor molar ratio type; (B) H3PO4, PTCA and Fe 3+The molar ratios are (a) 1:1:0.8, (b) 1.1:1:0.8, (c) 1.2:1:0.8, (d) 1.3:1:0.8 and (e) 1.4:1:0.8, and (f) 1.5:1:0.8; (C) is the synthesis temperature of De-Fe(Ⅲ)-PTCA MOFs; (D) is the synthesis time of De-Fe(Ⅲ)-PCCA MOFs.
[0029] Fig. 9 Optimization of De-Fe(Ⅲ)-PTCA MOFs / S2O8 for electrochemiluminescence test conditions 2- Optimization of the test conditions of the luminophore, where (A) is the excitation potential; (B) is the scan rate; (C) is the De-Fe(Ⅲ)-PCA MOFs / S2O8 2- incubation concentration.
[0030] Fig.10 Commercialization of Ruthenium Bipyridine / S2O8 2- (-0.3~-1.2 V voltage trigger), PTCA / S2O8 2- Luminescent body (-0.3V voltage trigger), Fe(III)-PCCA MOFs / S2O8 of comparative example 1 2- Luminescent body (-0.3 V voltage trigger) and De-Fe(III)-PTCA MOFs / S2O8 of Example 1 2- Electrochemiluminescence intensity-time curve of the luminophore (-0.3 V voltage trigger).
[0031] Fig.11 De-Fe(III)-PTCA MOFs / S2O8 of Example 1 2- (-0.3 V voltage trigger) Electrochemiluminescence performance and commercialized Ruthenium bipyridine / S2O8 2- (-1.2 V voltage trigger), PTCA / S2O8 2 (-0.3 V voltage trigger) and Fe(Ⅲ)-PTCA MOFs / S2O8 of Comparative Example 1 2- (-0.3 V voltage trigger) performance comparison chart.
[0032] Fig.12 Commercialization of Ruthenium Bipyridine / S2O8 2- (-1.0 V voltage trigger), PTCA / S2O8 2- Luminescent body (-0.3 V voltage trigger), Fe(Ⅲ)-PCCA MOFs / S2O8 of comparative example 1 2- Luminescent body (-0.3 V voltage trigger) and De-Fe(III)-PTCA MOFs / S2O8 of Example 1 2-Comparison of the electrochemiluminescence performance of the luminophores (triggered by -0.3 V voltage).
[0033] Fig.13 De-Fe(III)-PTCA MOFs / S2O8 prepared in Example 1 2- Electrochemiluminescence intensity-time curve of the luminophore.
[0034] Fig.14 This is a comparison chart of the normalized fluorescence and electrochemiluminescence spectra of De-Fe(III)-PTCA MOFs prepared in Example 1.
[0035] Fig.15 Comparison of the normalized fluorescence and electrochemiluminescence spectra of Fe(Ⅲ)-PTCA MOFs (A) and PTCA (B).
[0036] Fig.16 This is a comparison chart of the fluorescence intensities of De-Fe(III)-PTCA MOFs prepared in Example 1, Fe(III)-PTCA MOFs prepared in Comparative Example 1, and PTCA.
[0037] Fig.17 It is a comparison chart of the X-ray diffraction spectra of De-Fe(III)-PTCA MOFs prepared in Example 1, Fe(III)-PTCA MOFs prepared in Comparative Example 1, and PTCA.
[0038] Fig.18 The differential pulse voltammetry (DPV) curves are shown in Figure 1, where (a) is the De-Fe(III)-PTCA MOFs prepared in Example 1 in phosphate buffer; (b) is the De-Fe(III)-PTCA MOFs prepared in Example 1 in a solution containing S2O8 2- Differential pulse voltammetry curves in phosphate buffer.
[0039] Fig.19 For De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- Electrochemiluminescence intensity diagram of the binary system under different carboxylesterase catalyzed substrates.
[0040] Fig. 20 For De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- Comparison of the electrochemiluminescence performance of carboxylesterase catalysis in the presence of different substrates in the binary system.
[0041] Fig.21 The diagrams show the binding modes of different substrates with carboxylesterase, where (A) is phenyl acetate; (B) is phenyl propionate; and (C) is 1-naphthyl acetate.
[0042] Fig. 22The electrochemiluminescence intensity diagram of De-Fe(III)-PTCA MOFs in the present invention in different carboxylesterase activities, where (a) is 1×10 -6 U / L; (b) is 1×10 -5 U / L; (c) is 1×10 -4 U / L; (d) is 1×10 -3 U / L; (e) is 1×10 -2 U / L; (f) is 1×10 -1 U / L; (g) is 1 U / L.
[0043] Fig.23 This is the working curve of the De-Fe(III)-PTCA MOFs of the present invention for detecting carboxylesterases with different activities.
[0044] Fig.24 This is the anti-interference detection experiment of De-Fe(III)-PTCA MOFs of the present invention. DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Unless otherwise specified, the experimental methods used in the following experimental examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0047] Example 1 The synthesis method of the defect-rich perylene-based metal organic framework material of this embodiment is as follows: Figure 1 As shown, it includes the following steps: 400 μL of Fe(NO3)3·9H2O (34.98 mmol / L), PTCA (0.018 mmol) and H3PO4 (0.023 mmol) modifier aqueous solution was added to the reactor, and then deionized water was added to make the total volume 2 mL. The resulting mixture was thoroughly mixed under ultrasound for 5 minutes and then heated in an oven at 110 °C for 4 hours. The obtained sample was centrifuged and purified with ultrapure water for 4 times to obtain the defect engineering mediated ultra-low potential near-infrared electrochemiluminescent body, and the obtained product was named De-Fe(Ⅲ)-PTCA MOFs and dried under vacuum for subsequent use.
[0048] Comparative Example 1 The synthesis method of the perylene-based metal organic framework material of this comparative example is different from that of Example 1 in that it does not contain an acid regulator, and comprises the following steps: 400 μL of Fe(NO3)3·9H2O (34.98 mmol / L) and PTCA (0.018 mmol) were added to the reactor, and then deionized water was added to make the total volume 2 mL. The resulting mixture was thoroughly mixed under ultrasound for 5 minutes and then heated in an oven at 110 °C for 4 hours. The obtained sample was centrifuged and purified with ultrapure water 4 times. The obtained product was named Fe(Ⅲ)-PTCA MOFs and dried under vacuum for subsequent use.
[0049] Scanning electron microscope SEM shows that De-Fe(Ⅲ Fig. 9 Optimization of De-Fe(Ⅲ)-PTCA MOFs / S2O8 for electrochemiluminescence test conditions 2- Optimization of the test conditions of the luminophore, where (A) is the excitation potential; (B) is the scan rate; (C) is the De-Fe(Ⅲ)-PCA MOFs / S2O8 2- incubation concentration.
[0050] Fig.10 Commercialization of Ruthenium Bipyridine / S2O8 2- (-0.3~-1.2 V voltage trigger), PTCA / S2O8 2- Luminescent body (-0.3V voltage trigger), Fe(III)-PCCA MOFs / S2O8 of comparative example 1 2- Luminescent body (-0.3 V voltage trigger) and De-Fe(III)-PTCA MOFs / S2O8 of Example 1 2- Electrochemiluminescence intensity-time curve of the luminophore (-0.3 V voltage trigger).
[0051] Fig.11 De-Fe(III)-PTCA MOFs / S2O8 of Example 1 2- (-0.3 V voltage trigger) Electrochemiluminescence performance and commercialized Ruthenium bipyridine / S2O8 2- (-1.2 V voltage trigger), PTCA / S2O8 2 (-0.3 V voltage trigger) and Fe(Ⅲ)-PTCA MOFs / S2O8 of Comparative Example 1 2- (-0.3 V voltage trigger) performance comparison chart.
[0052] Fig.12 Commercialization of Ruthenium Bipyridine / S2O8 2- (-1.0 V voltage trigger), PTCA / S2O82- Luminescent body (-0.3 V voltage trigger), Fe(Ⅲ)-PCCA MOFs / S2O8 of comparative example 1 2- Luminescent body (-0.3 V voltage trigger) and De-Fe(III)-PTCA MOFs / S2O8 of Example 1 2- Comparison of the electrochemiluminescence performance of the luminophores (triggered by -0.3 V voltage).
[0053] Fig.13 De-Fe(III)-PTCA MOFs / S2O8 prepared in Example 1 2- Electrochemiluminescence intensity-time curve of the luminophore.
[0054] Fig.14 This is a comparison chart of the normalized fluorescence and electrochemiluminescence spectra of De-Fe(III)-PTCA MOFs prepared in Example 1.
[0055] Fig.15 Comparison of the normalized fluorescence and electrochemiluminescence spectra of Fe(Ⅲ)-PTCA MOFs (A) and PTCA (B).
[0056] Fig.16 This is a comparison chart of the fluorescence intensities of De-Fe(III)-PTCA MOFs prepared in Example 1, Fe(III)-PTCA MOFs prepared in Comparative Example 1, and PTCA.
[0057] Fig.17 It is a comparison chart of the X-ray diffraction spectra of De-Fe(III)-PTCA MOFs prepared in Example 1, Fe(III)-PTCA MOFs prepared in Comparative Example 1, and PTCA.
[0058] Fig.18 The differential pulse voltammetry (DPV) curves are shown in Figure 1, where (a) is the De-Fe(III)-PTCA MOFs prepared in Example 1 in phosphate buffer; (b) is the De-Fe(III)-PTCA MOFs prepared in Example 1 in a solution containing S2O8 2- Differential pulse voltammetry curves in phosphate buffer.
[0059] Fig.19 For De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- Electrochemiluminescence intensity diagram of the binary system under different carboxylesterase catalyzed substrates.
[0060] Fig. 20 For De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- Comparison of the electrochemiluminescence performance of carboxylesterase catalysis in the presence of different substrates in the binary system.
[0061] Fig.21 The diagrams show the binding modes of different substrates with carboxylesterase, where (A) is phenyl acetate; (B) is phenyl propionate; and (C) is 1-naphthyl acetate.
[0062] Fig. 22 The electrochemiluminescence intensity diagram of De-Fe(III)-PTCA MOFs in the present invention in different carboxylesterase activities, where (a) is 1×10 -6 U / L; (b) is 1×10 -5 U / L; (c) is 1×10 -4 U / L; (d) is 1×10 -3 U / L; (e) is 1×10 -2 U / L; (f) is 1×10 -1 U / L; (g) is 1 U / L.
[0063] Fig.23 This is the working curve of the De-Fe(III)-PTCA MOFs of the present invention for detecting carboxylesterases with different activities.
[0064] Fig.24 This is the anti-interference detection experiment of De-Fe(III)-PTCA MOFs of the present invention. DETAILED DESCRIPTION
[0065] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] Unless otherwise specified, the experimental methods used in the following experimental examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0067] Example 1 The synthesis method of the defect-rich perylene-based metal organic framework material of this embodiment is as follows: Figure 1 As shown, it includes the following steps: 400 μL of Fe(NO3)3·9H2O (34.98 mmol / L), PTCA (0.018 mmol) and H3PO4 (0.023 mmol) modifier aqueous solution was added to the reactor, and then deionized water was added to make the total volume 2 mL. The resulting mixture was thoroughly mixed under ultrasound for 5 minutes and then heated in an oven at 110 °C for 4 hours. The obtained sample was centrifuged and purified with ultrapure water for 4 times to obtain the defect engineering mediated ultra-low potential near-infrared electrochemiluminescent body, and the obtained product was named De-Fe(Ⅲ)-PTCA MOFs and dried under vacuum for subsequent use.
[0068] Comparative Example 1 The synthesis method of the perylene-based metal organic framework material of this comparative example is different from that of Example 1 in that it does not contain an acid regulator, and comprises the following steps: 400 μL of Fe(NO3)3·9H2O (34.98 mmol / L) and PTCA (0.018 mmol) were added to the reactor, and then deionized water was added to make the total volume 2 mL. The resulting mixture was thoroughly mixed under ultrasound for 5 minutes and then heated in an oven at 110 °C for 4 hours. The obtained sample was centrifuged and purified with ultrapure water 4 times. The obtained product was named Fe(Ⅲ)-PTCA MOFs and dried under vacuum for subsequent use.
[0069] Scanning electron microscope SEM shows that De-Fe(Ⅲ) prepared in Example 1 The synthesis method of the defect-rich perylene-based metal organic framework material in this example is different from that in Example 1 in that Fe 3+ De-Fe(III)-PTCA MOFs were prepared with a molar ratio of 0.2:1, 0.5:1, 0.7:1, 0.9:1 and 1:1 to PTCA precursor.
[0070] By comparing Example 1 and this example with different Fe 3+ The defect-rich perylene-based metal-organic framework material prepared by the molar ratio of PTCA precursor was tested by electrochemiluminescence spectrometry to screen out the optimal molar ratio of the two. 2- In the air-saturated 0.1 mol / L phosphate buffer (pH 7.4) of the coreaction reagent, 1 mol / L of the perylene-based metal-organic framework material prepared in this example was used to collect the ECL intensity at a potential scan from 0 V to -0.3 V. The results showed that when Fe 3+ When the molar ratio of PTCA is 4:5 ( Figure 8 A), De-Fe(Ⅲ)-PTCA MOFs has the highest ECL signal.
[0071] Example 8 The method for synthesizing defect-rich perylene-based metal organic framework materials in this embodiment is different from that in Example 1 in that H3PO4 / PTCA / Fe 3+ De-Fe(III)-PTCA MOFs were prepared with molar ratios of 1:1:0.8, 1.1:1:0.8, 1.2:1:0.8, 1.4:1:0.8 and 1.5:1:0.8.
[0072] By comparing the results of Example 1 and this example with different H3PO4 / PTCA / Fe 3+ The defect-rich perylene-based metal-organic framework material prepared by the molar ratio of 20 mmol / L S2O8 was tested by electrochemiluminescence spectrometry to screen out the optimal molar ratio of the three. 2- In the air-saturated 0.1 mol / L phosphate buffer (pH 7.4) of the coreaction reagent, 1 mol / L of the perylene-based metal organic framework material prepared in this example was used to collect the ECL intensity by potential scanning from 0 V to -0.3 V. The results showed that H3PO4 and PTCA, Fe 3+ The optimal molar ratio is 1.3:1:0.8 ( Figure 8 B).
[0073] Example 9 The method for synthesizing defect-rich perylene-based metal organic framework materials in this embodiment is different from that in Example 1 in that De-Fe(III)-PTCAMOFs are prepared by heating in an oven at 80°C, 90°C, 100°C, 120°C, 130°C and 140°C for 4 hours, respectively.
[0074] The defect-rich perylene-based metal organic framework materials prepared at different temperatures in Example 1 and this example were tested by electrochemical luminescence spectrometer to screen out the optimal temperature. 2- In the air-saturated 0.1 mol / L phosphate buffer (pH 7.4) of the coreaction reagent, 1 mol / L of the perylene-based metal-organic framework material prepared in this example was used to collect the ECL intensity by potential scanning from 0 V to -0.3 V. The results showed that the optimal synthesis temperature was 110°C ( Figure 8 C).
[0075] Example 10 The method for synthesizing the defect-rich perylene-based metal organic framework material of this embodiment is different from that of Example 1 in that De-Fe(III)-PTCA MOFs are prepared by heating in an oven at 110° C. for 1 hour, 2 hours, 3 hours, 5 hours and 6 hours, respectively.
[0076] The defect-rich perylene-based metal organic framework materials prepared by different heating methods in Example 1 and this example were tested by electrochemical luminescence spectrometer to screen out the optimal synthesis time. 2- In the air-saturated 0.1 mol / L phosphate buffer (pH 7.4) of the coreaction reagent, 1 mol / L of the perylene-based metal-organic framework material prepared in this example was used, and the ECL intensity was collected by potential scanning from 0 V to -0.3 V. The results showed that the optimal synthesis time was 4 hours ( Figure 8 D).
[0077] The above optimization results of the synthesis conditions show that the ultra-low potential near-infrared electrochemical luminescent material mediated by defect engineering prepared in Example 1 has the best ECL signal.
[0078] Implementation effect example Optimization of electrochemiluminescence test conditions for De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- The test conditions of the luminous body are optimized, and the results are as follows Fig.10 In the presence of 0.3 mmol / L 1-naphthyl acetate (1-NA, CE specific substrate) and 20 mmol / L S2O8 2- The carboxylesterase (CE) sample was added to a 0.1 mol / L PBS test solution of the co-reactant. The sample was vigorously stirred and incubated at 25°C for 30 minutes before analysis. Then, 5 μL of De-Fe(III)-PTCA MOFs prepared in Example 1 was added dropwise to a glassy carbon electrode (GCE, Φ =3 mm), the prepared De-Fe-PTCA MOFs|GCE was used as the working electrode to detect the CE activity. In addition, Ag / AgCl (saturated KCl) was used as the reference electrode and Pt wire was used as the counter electrode. The ECL signal was collected by cyclic voltammetry (CV). The results show that the optimal excitation potential ( Fig. 9 A), scanning rate ( Fig. 9 B) and incubation volume ( Fig. 9 C) are -0.3 V, 300 mV / S, and 1 mg / mL, respectively.
[0079] Due to Ru(bpy)3Cl2 / S2O8 2- The standard cannot generate ECL at -0.3 V, so Ru(bpy)3Cl2 / S2O8 with a higher excitation potential at -1.2 V was selected. 2- The ECL signal of the luminophore was used as the standard, while the De-Fe(Ⅲ)-PTCAMOFs / S2O8 2-、Fe(Ⅲ)-PTCA-MOFs / S2O8 2- and PTCA / S2O8 2- The ECL signals were collected in the scanning potential range from 0 to -0.3 V. Even in this unfair situation, De-Fe(Ⅲ)-PCA MOFs / S2O8 2- The luminophore also showed the highest ECL efficiency of 553.06% ( Fig.10 , 11), respectively, compared with the original Fe(Ⅲ)-PTCA MOFs / S2O8 2- and PTCA / S2O8 2- The luminescent material is 2.65 times and 5.30 times higher. 2- Luminescent signal as standard, De-Fe(Ⅲ)-PTCAMOFs / S2O8 2- The system showed the highest ECL efficiency of 2463.90% ( Fig.12 ).
[0080] In addition, at an ultra-low trigger potential of -0.3 V, De-Fe(Ⅲ)-PTCAMOFs / S2O8 2- The ECL of the luminophore remained stable over 43 consecutive cycles with a relative standard deviation of only 0.90% ( Fig.13 ).
[0081] The above results show that De-Fe(III) / PTCA MOFs / S2O8 can be obtained through the acid-assisted defect engineering strategy. 2- Ultra-low potential triggering of the luminophore, highly repeatable and stable ECL, reduces interference for trace sensing applications.
[0082] De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- The luminophore exhibited near-infrared ECL emission (maximum = 728 nm, Fig.14 ), which is different from Fe(Ⅲ)-PTCA MOFs / S2O8 2- The peak ECL value of the luminophore (maximum value = 717 nm, Fig.15 A) and PTCAMOFs / S2O8 2- (Max = 720 nm, Fig.15 B) is different, which is attributed to the effect of H3PO4 modifier, providing opportunities for lower background interference and longer penetration depth sensing and imaging.
[0083] It is noteworthy that the FL emission wavelength of De-Fe(Ⅲ)-PTCA MOFs is similar to that of Fe(Ⅲ)-PTCA MOFs and PTCA aggregates. However, compared with PTCA aggregates, the intensities of De-Fe(Ⅲ)-PTCA MOFs and Fe(Ⅲ)-PTCA MOFs are 1.23 times and 1.17 times higher ( Fig.16 This phenomenon is due to the inherent porous structure of MOF, which leads to a reduced ACQ effect and thus enhances the radiative luminescence efficiency of De-Fe(Ⅲ)-PTCA MOFs.
[0084] In addition, the powder X-ray diffraction (PXRD) patterns of De-Fe(Ⅲ)-PTCA MOFs are similar to those of Fe(Ⅲ)-PTCA MOFs and PTCA aggregates ( Fig.17 ) diagram is similar, but the peak intensity of De-Fe(Ⅲ)-PTCAMOFs at 12.3° is related to the edge-to-face π-π stacking of the (020) plane and the peak intensity at 27.5° corresponds to ( ) faces are all lower than those of Fe(Ⅲ)-PTCA MOFs and PTCA aggregates, which further indicates that the reduction of intermolecular π-π stacking in De-Fe(Ⅲ)-PTCA MOFs leads to the improvement of emission efficiency.
[0085] The differential pulse voltammetry curves of De-Fe(Ⅲ)-PTCA MOFs have lower reduction peaks and more obvious reduction currents than those of Fe(Ⅲ)-PTCA-MOF. Fig.18 a), which indicates that electrons are more easily and rapidly injected into the lowest unoccupied molecular orbital of De-Fe(III)-PTCA MOFs than those of Fe(III)-PTCA-MOFs, which may be due to the fact that the structural defects induce more open metal sites, making it easier for electrons to be injected.
[0086] It is worth noting that when using De-Fe(Ⅲ)-PTCA MOFs / GCE, S2O8 2- Generate SO4 •- The reduction peak of S2O8 on the bare electrode is significantly reduced to -0.25 V. 2- The maximum reduction peak potential is -1.12 V ( Fig.18 b), a sharp shift of 0.87 V, and the current intensity is significantly enhanced compared with Fe(Ⅲ)-PTCAMOFs / GCE and bare GCE. DPV results show that De-Fe(Ⅲ)-PTCA MOFs with more open metal sites are more sensitive to S2O8 2- De-Fe(Ⅲ)-PTCAMOFs / S2O8 has excellent electrocatalytic activity. 2-The main reason why the system has ultra-low trigger potential ECL.
[0087] Therefore, the highest ECL efficiency of De-Fe(III)-PTCA MOFs is attributed to the reduction of ACQ (to improve the emission efficiency) and the addition of S2O8 2- Significant electrocatalytic activity of the co-reactants (to trigger efficient electrochemical excitation processes).
[0088] Application Examples Studies have shown that the difference in carboxylesterase between hepatocellular carcinoma and cirrhosis is significantly more significant than AFP, and it is a potential effective serological biomarker for hepatocellular carcinoma. Although commercial kits have achieved colorimetric detection of carboxylesterase activity, their sensitivity is relatively low. In recent years, various fluorescent probes have been designed for highly sensitive detection of carboxylesterase activity, but these probes have low selectivity in complex biological matrices and are prone to photobleaching. Electrochemiluminescence analysis technology has the outstanding advantages of easy operation, high sensitivity and easy integration, providing an opportunity for highly sensitive detection of CE activity. Based on this, this patent constructs a sensitive label-free signal ECL sensor for measuring carboxylesterase activity by acid-regulated induced defect ultra-low potential triggering near-infrared electrochemiluminescence luminophores.
[0089] The specific detection of carboxylesterase activity relies on the intelligent signal conversion triggered by CE. Phenyl acetate (PA), 1-naphthyl acetate, phenyl propionate (PP) and 1-naphthyl propionate (1-NP) were screened as potential substrates due to the inherently efficient hydrolysis behavior of CE on ester groups.
[0090] In the absence of CE, PA, 1-NA and PP have a significant effect on the performance of De-Fe(Ⅲ)-PTCA MOFs / S2O8 2- The binary system had no effect, while 1-NP significantly reduced the 2- The ECL signal ( Fig.19 ). Therefore, 1-NP cannot meet the basic conditions, that is, there is no CE effect, and the substrate cannot quench the ECL signal of De-Fe(Ⅲ)-PTCA MOFs.
[0091] Compared with PA and PP as substrates, 1-NA significantly quenched the activity of De-Fe(Ⅲ)-PTCA MOFs / S2O8 in the presence of 0.1 U / L CE. 2- The ECL intensity ( Fig. 20The affinity of PA, 1-NA, PP and CE (PDB: 1MX5) was evaluated by molecular docking simulation. The binding free energy of 1-NA (-7.7 kcal / mol) was lower than that of PP (-6.816 kcal / mol) and PA (-6.562 kcal / mol), which is consistent with the binding free energy of 1-NA (-7.7 kcal / mol) and 1-NA (-6.816 kcal / mol) and 1-NA (-6.562 kcal / mol), which is consistent with the binding free energy of 1-NA (-7.7 ...816 kcal / mol) and 1-NA (-6.562 kcal / mol), which is consistent with the binding free energy of 1-NA (-7. 2- The strong interaction between 1-NA and CE is attributed to the formation of hydrogen bonds with GLY-1142 and GLY-1143, as well as strong hydrophobic interactions with ILE-1359, LEU-1363, LEU-1097, LEU-1304, and PHE-1101 on the CE protein, which makes 1-NA have a good affinity with CE ( Fig.21 ).
[0092] Taking the De-Fe(III)-PTCA MOFs prepared in Example 1 as an example, it was applied to the detection of the activity of the biomarker carboxylesterase of liver cancer cells: A biosensor is constructed as follows: different activities (ranging from 1×10 -6 U / L to 1 U / L) of carboxylesterase samples were added to a solution containing 0.3 mmol / L 1-naphthyl acetate (a specific substrate for carboxylesterase) and 20 mmol / L S2O8 2- The coreactants were mixed in a 0.1 mol / L PBS test solution. Samples were stirred vigorously and then incubated at 25°C for 30 min prior to analysis.
[0093] Subsequently, 5 μL of De-Fe(III)-PTCA MOFs (1 mg / mL) prepared in Example 1 was added dropwise to the glassy carbon electrode (GCE, Φ =3 mm) as the working electrode to detect the CE activity. In addition, Ag / AgCl (saturated KCl) was used as the reference electrode and Pt wire was used as the counter electrode. Unless otherwise stated, the ECL signals were collected by cyclic voltammetry (CV) with a scan range of 0 to -0.3 V at a rate of 300 mV / s.
[0094] The results showed that as the activity of carboxylesterase increased, the kinetics of naphthol generated by the hydrolysis of 1-naphthyl acetate accelerated, and the electrochemiluminescence intensity decreased sharply ( Fig. 22 ).
[0095] The logarithm of carboxylesterase activity (log C CEL ) is the horizontal axis, and the electrochemiluminescence intensity is compared with the blank intensity reduction value (Δ I ECL = Iblank - I ) is used as the ordinate to draw a graph and obtain the working curve ( Fig.23 ); Fig.23 The results show that the linear regression equation is: Δ I ECL =2051.20 lg(c / U·L -1 )+13045.89( R 2 =0.996). The established lg C CE Compared with the electrochemiluminescence intensity, the blank intensity reduction value has a good linear relationship. The detection limit of the carboxylesterase activity of the sensor is 6.6×10 -7 U / L.
[0096] Glucose, bovine serum albumin (BSA), and glucose oxidase (GOX) phosphate buffer solutions with a concentration of 1 g / L were prepared as interfering substances to study the selectivity of the sensor, and carboxylesterase phosphate buffer solution was used as a control. Compared with the blank sample, the effects of these interferences were negligible even at a higher concentration (1 g / L) (see Fig.24 ), reflecting the strong specific response ability of the electrochemiluminescence sensor.
[0097] Therefore, the defect-rich, electron-deficient perylene-based metal-organic framework materials prepared by the acid regulator-induced defect strategy were used as emitters and 1-naphthyl acetate was used as the catalytic substrate to construct a highly sensitive and specific carboxylesterase sensor, opening up a promising avenue for the early diagnosis of hepatocellular carcinoma.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-low potential near-infrared electrochemical luminescent body mediated by defect engineering, characterized in that: The method comprises the following steps: mixing 3, 4, 9, 10-perylenetetracarboxylic acid, a transition metal salt solution and an acid regulator aqueous solution, and then subjecting the mixture to a hydrothermal reaction to obtain the product.
2. The preparation method according to claim 1, characterized in that: The transition metal ions in the transition metal salt solution are Fe(II), Cu(II), Co(II), Fe(III) or Zn(II); and the acid regulator is phosphoric acid, acetic acid, formic acid, hydrochloric acid, trifluoroacetic acid or benzoic acid.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the 3, 4, 9, 10-perylenetetracarboxylic acid, the transition metal ion and the acid regulator is 1:(0.2-1):(1-1.5).
4. The preparation method according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 80-140° C. and the time is 1-6 hours.
5. An ultra-low potential near-infrared electrochemical luminescent body prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the ultra-low potential near-infrared electrochemiluminescent substance according to claim 5 in the detection of carboxylesterase activity.
7. A biosensor, characterized in that: The working electrode of the biosensor comprises the ultra-low potential near-infrared electrochemical luminescent substance as claimed in claim 5.
8. Use of the biosensor according to claim 7 in detecting carboxylesterase activity.
9. The use according to claim 8, characterized in that: The method comprises the following steps: adding a carboxylesterase sample into a solution containing a catalytic substrate and a co-reaction reagent, incubating the solution, and detecting the electrochemical luminescence intensity by using the biosensor.
10. The use according to claim 9, characterized in that: The catalytic substrate is 1-naphthyl acetate; the co-reaction reagent is a salt containing persulfate.